2017
DOI: 10.1371/journal.pone.0189152
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the boundaries for early caffeine initiation in neonatal practice: Results of a prospective, multicenter study on very preterm infants with respiratory distress syndrome

Abstract: BackgroundThere is growing evidence that supports the benefits of early use of caffeine in preterm neonates with RDS; however, no formal recommendations specifying the exact timing of therapy initiation have been provided.ObjectivesWe compared neonatal outcomes in infants receiving early (initial dose on the 1st day of life) and late (initial dose on day 2+ of life) caffeine therapy.MethodsUsing data from a prospective, cohort study, we identified 986 infants ≤32 weeks’ gestation with RDS and assessed the timi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 20 publications
3
26
0
3
Order By: Relevance
“…The authors concluded that early caffeine was associated with a decreased need for invasive ventilation and significantly shorter duration of mechanical ventilation, compared to late caffeine. However, there was no difference in the rates of BPD and death between the early and late treatment groups . Comparable to their study, the rates of BPD were similar in our neonatal units, despite a tendency to give caffeine earlier in the UK, compared to Germany.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The authors concluded that early caffeine was associated with a decreased need for invasive ventilation and significantly shorter duration of mechanical ventilation, compared to late caffeine. However, there was no difference in the rates of BPD and death between the early and late treatment groups . Comparable to their study, the rates of BPD were similar in our neonatal units, despite a tendency to give caffeine earlier in the UK, compared to Germany.…”
Section: Discussionmentioning
confidence: 77%
“…5 Several studies, including a post hoc analysis of the CAP trial, 12 have shown advantages of early initiation of caffeine in very low birth weight (VLBW) infants. [13][14][15][16][17][18] In view of these benefits, early caffeine has become an important part of newborn respiratory care to minimise mechanical ventilation. 2 Early caffeine is increasingly being used as an adjunctive therapy to other interventions, like early continuous positive airway pressure in the management of respiratory distress syndrome in order to reduce lung injury in preterm infants.…”
mentioning
confidence: 99%
“…A small pilot double-blinded, randomised, placebo-controlled trial conducted in 2015 on 21 infants (<29 GW) randomised to early prophylactic use of caffeine (<2 h of age) or to later caffeine initiation (at 12 h of age), reported improved blood pressure and systemic blood flow (significantly higher superior vena cava flow and right ventricular output) in the early group, and a trend towards reduced rates of intubation by 12 h of age (27% versus 70%; p=0.08), but no reduction in the number of days of mechanical ventilation [40]. More recently, a prospective cohort study on 986 infants (⩽32 GW) with respiratory distress syndrome demonstrated that early caffeine treatment (<24 h after birth) compared to later treatment (⩾2 days) was associated with a significantly reduced need for invasive ventilation, total duration of mechanical ventilations and significantly lower odds of intraventricular haemorrhage (IVH) and PDA, but no difference in the incidence of BPD and mortality rates [63]. Finally, in a small cohort randomised study, DEKKER et al [12] demonstrated benefits of caffeine administered in the delivery room on minute volumes and tidal volumes at 7-9 min after birth compared to caffeine given after arrival in the neonatal intensive care unit.…”
Section: Bpd and Long-term Pulmonary Outcomesmentioning
confidence: 99%
“…Early caffeine administration (initial dose on the 1st day of life) in very preterm neonates improved outcomes, reduced the need for invasive ventilation and total duration of mechanical ventilation and decreased future complications, such as intraventricular hemorrhage, patent ductus arteriosus (PDA), and bronchopulmonary dysplasia (BPD) . These effects may be attributed to broad anti‐inflammatory properties, the ability to stimulate breathing and increase sensitivity to CO 2 , improvement in hemodynamics and in cerebral blood flow, as well as to antagonism of several prostaglandins …”
Section: Respiratory Distress In the Neonatesmentioning
confidence: 99%
“…Methylxanthines generally act as stimulants of CNS and as stimulators of respiratory drive, lowering the threshold of sensitivity to hypercapnia, increasing the contractility of the diaphragm, and facilitating weaning off mechanical ventilation . As the pioneering “Caffeine for Apnea of Prematurity (CAP)” trial, the effects of caffeine on the incidence of AOP, BPD, retinopathy of prematurity, and PDA have been confirmed in many studies . The standard dosing regimes of caffeine citrate include an intravenous loading dose of 20 mg/kg followed by a maintenance dose of 5 mg/kg/day .…”
Section: Respiratory Distress In the Neonatesmentioning
confidence: 99%